TÜRKİYE’DE İNŞAAT SEKTÖRÜNDE YAŞANAN İŞ KAZALARI VE ÖLÜMLÜ İŞ KAZASI SAYILARININ TAHMİNİ - (:unkn) unknown (My University, 2018)
Teknolojide yaşanan gelişmelerle birlikte iş hayatında karşılaşılabilecek tehlikeler de artmaktadır. Bu durumişyerlerinde iş sağlığı ve güvenliği önlemlerinin alınmasının önemini göstermektedir. Ülkemizde her yıl farklısektörlerde çeşitli sebeplerle birçok iş kazası ve meslek hastalığı vakaları yaşanmaktadır. İnşaat sektörü, madenve ulaşım sektörleri ile birlikte en çok iş kazasının yaşandığı sektördür. Bu çalışmada Sosyal GüvenlikKurumu’ndan alınan verilerle ülkemizde inşaat sektöründe yaşanan iş kazası sayıları incelenmiştir. İnşaatsektöründe 2007-2015 yıllarına ait veriler kullanılarak henüz verileri açıklanmamış olan 2016 yılına ait iş kazasıve ölümlü iş kazası sayılarının tahmin edilmesi amaçlanmıştır. Tahmin yöntemi olarak üssel düzleştirme yöntemikullanılmıştır. Yapılan tahmin sonucunda 2008-2015 yılları için öngörülen değerlerin gerçekleşen iş kazasısayılarına yakın değerlerde seyretmesi ve sapma değerlerinin düşük olması 2016 yılı için yapılan tahminin dedoğruluk payının yüksek olduğunu göstermiştir.

With the technological developments, the danger that can be encountered in business life have also increased. This situation emphasizes the importance of taking occupational health and safety measures at workplaces. In our country, there are many work accidents and occupational diseases cases in different sectors every year. The construction sector, along with the mining and transportation sectors, is the sector where most of the work accident is experienced. In this study, the number of work accidents in the construction sector in our country which was taken from the Social Security Institution were examined. It was aimed to estimate the number of work accidents and deadly work accidents for the year 2016, which have not yet been announced, by using data for 2007-2015 in the construction sector. The exponential smoothing method was used as the estimation method. As a result of the estimation, it was seen that the estimate for year of 2016 had a high accuracy because the values foreseen for the work accidents in 2008-2015 were close to the real number of work accidents and the deviation values were low between real values and foreseen values.
ESTIMATION OF THE NUMBER OF WORK ACCIDENT AND DEADLY WORK ACCIDENT ENCOUNTERED IN CONSTRUCTION SECTOR IN TURKEY
Keywords: Tarih